Development of an Ethnoscience-Based Teaching Module on Incung Kerinci Batik as a Learning Resource for Biology of Plant Material (Plantae) - Lega Anattri; Upik Yelianti; Agus Subagyo (Postgraduate, University of Mataram, 2024)
Ethnoscience can be used and integrated into various learning models, one of which is the 21st century learning model in the form of a Project based learning (PjBL) learning model with an ethnoscience approach. This research was conducted in Kerinci Regency and Sungai Banyak City, precisely at SMA Negeri 1 Sungai Banyak and the Kerinci Incung batik studio, this study aims to produce ethnoscience-based teaching modules that can improve students' understanding of plants through a local cultural approach. The research method used is the ADDIE development model, the results of the material expert validation were 98.60% and the results of the media expert validation were 96.30% with a very valid category and feasible to be applied. Continued with product trials using random sampling data collection techniques and involving classes XA and % with practical and very practical categories. Practicality tests were also conducted on six biology teachers in class X obtained with percentages, namely: 75%; 100%; 91.25%; 93.75%; 89.16%; and 95.41% with an average category of very practical